2020
DOI: 10.1134/s1022795420080086
|View full text |Cite
|
Sign up to set email alerts
|

Association of CRP, CD14, Pro-Inflammatory Cytokines and Their Receptors (TNFA, LTA, TNFRSF1A, TNFRSF1B, IL1B, and IL6) Genes with Chronic Obstructive Pulmonary Disease Development

Abstract: The aim of the present study was to investigate the association of COPD and frequent exacerbator COPD phenotype with CRP, CD14, and pro-inflammatory cytokines and their receptors (TNFA, LTA, TNFRSF1A, TNFRSF1B, IL1B, and IL6) genes. It was found that COPD was associated with allele A of the TNFA gene (rs1800629G>A)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The lincRNA_2411 .6 was 11 × over-expressed in the mastitic samples compared to the healthy samples (FC = 11.31, FDR = 3.19E-02) and is predicted to interact with TNFRSF1A which is located upstream. This receptor encodes the type 1 receptor for tumor necrosis factor - α (TNFα) 58 , which is a pro-inflammatory cytokine secreted by inflammatory cells 59 . Numerous studies have investigated TNF α in relation to mastitis and have found that concentrations increase during mastitis caused by E .…”
Section: Resultsmentioning
confidence: 99%
“…The lincRNA_2411 .6 was 11 × over-expressed in the mastitic samples compared to the healthy samples (FC = 11.31, FDR = 3.19E-02) and is predicted to interact with TNFRSF1A which is located upstream. This receptor encodes the type 1 receptor for tumor necrosis factor - α (TNFα) 58 , which is a pro-inflammatory cytokine secreted by inflammatory cells 59 . Numerous studies have investigated TNF α in relation to mastitis and have found that concentrations increase during mastitis caused by E .…”
Section: Resultsmentioning
confidence: 99%